Influence of shade regimes on yield and quality of ginger (Zingiber officinale Rosc.) - Jayachandran, K Ajithkumar, B K (Journal of Spices and Aromatic Crops, 2003)
The effect of different levels of shade on yield and quality of ginger (Zingiber officinale Rosc.) was studied during two seasons at Coconut Research Station, Thiruvananthapuram, Kerala Agricultural University, Kerala. The shade levels 20 and 40 per cent were favourable for obtaining higher dry ginger yield. Volatile oil content showed an increasing trend with increasing levels of shade. Maximum NVEE was recorded in the plants grown under 20 and 40 per cent shade levels. Higher starch content was observed in plants grown under 20 per cent shade level. Crude fibre content gradually reduced as the intensity of shade increased. The results indicate the possibility of utilizing existing shaded situations in coconut gardens and under other perennial crops for the production of ginger.